Short acting insulin analogues in intensive care unit patients - Bilotta, Federico (Baishideng Publishing Group Inc, 2014)
Blood glucose control in intensive care unit (ICU) patients, addressed to actively maintain blood glucose concentration within defined thresholds, is based on two major therapeutic interventions: to supply an adequate calories load and, when necessary, to continuously infuse insulin titrated to patients needs: intensive insulin therapy (IIT). Short acting insulin analogues (SAIA) have been synthesized to improve the chronic treatment of patients with diabetes but, because of the pharmacokinetic characteristics that include shorter on-set and off-set, they can be effectively used also in ICU patients and have the potential to be associated with a more limited risk of inducing episodes of iatrogenic hypoglycemia. Medical therapies carry an intrinsic risk for collateral effects; this can be more harmful in patients with unstable clinical conditions like ICU patients. To minimize these risks, the use of short acting drugs in ICU patients have gained a progressively larger room in ICU and now pharmaceutical companies and researchers design drugs dedicated to this subset of medical practice. In this article we report the rationale of using short acting drugs in ICU patients (i.e., sedation and treatment of arterial hypertension) and we also describe SAIA and their therapeutic use in ICU with the potential to minimize iatrogenic hypoglycemia related to IIT. The pharmacodynamic and pharmachokinetic characteristics of SAIA will be also discussed.